2018
DOI: 10.1097/rli.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Photon Counting Computed Tomography With Dedicated Sharp Convolution Kernels

Abstract: A dedicated sharp convolution kernel for PCD CT imaging of coronary stents yields superior qualitative and quantitative image characteristics compared with conventional reconstruction kernels. Resulting higher noise levels in sharp kernel PCD imaging can be partially compensated with iterative image reconstruction techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 24 publications
3
59
0
Order By: Relevance
“…These have demonstrated not only the ability to produce images with higher spatial resolution, as expected from the smaller pixel size, but also the clinical value of such images. 10,12,[34][35][36][37] Higher spatial resolution is expected to improve the diagnostic quality in several CT applications, including imaging of the temporal bone, lung nodule characterization, visualization of calcified plaques, and imaging of bone fractures in trauma patients. 6 Here, we aim to demonstrate that deep silicon-based, photon-counting detectors offer similar benefits in terms of image resolution and thus that silicon may constitute a viable alternative for future photon-counting CT detectors.…”
Section: Introductionmentioning
confidence: 99%
“…These have demonstrated not only the ability to produce images with higher spatial resolution, as expected from the smaller pixel size, but also the clinical value of such images. 10,12,[34][35][36][37] Higher spatial resolution is expected to improve the diagnostic quality in several CT applications, including imaging of the temporal bone, lung nodule characterization, visualization of calcified plaques, and imaging of bone fractures in trauma patients. 6 Here, we aim to demonstrate that deep silicon-based, photon-counting detectors offer similar benefits in terms of image resolution and thus that silicon may constitute a viable alternative for future photon-counting CT detectors.…”
Section: Introductionmentioning
confidence: 99%
“…And thus, we still advise an appropriate dose of beta blocker for HR control, before the CCTA examination. About the technological advantages of these two CT devices, the 2nd generation (128-slice) dual-source CT (Siemens) is composed by two sets of independently operating X-ray tubes and 64 row detectors, it finishes a cardiac scanning at 280 ms 17. Using single sector reconstruction, the temporal resolution is 75 ms.…”
mentioning
confidence: 99%
“…In a phantom experiment, Symons et al [55] demonstrated significantly improved coronary stent lumen visibility with the "UHR mode". Von Spiczak et al [62] found superior qualitative and quantitative image characteristics for photon-counting coronary photon-counting detector image, "sharp mode", demonstrating higher spatial resolution and significantly improved visualization of bony structures. With permission from [26] stent imaging when using a dedicated sharp convolution kernel.…”
Section: Pre-clinical Evaluation Of Photon-counting Ctmentioning
confidence: 99%